1985
DOI: 10.1111/j.1469-7610.1985.tb00606.x
|View full text |Cite
|
Sign up to set email alerts
|

The Children's Depression Scale. A Study of Its Validity

Abstract: The validity of the Children's Depression Scale and of its parent-report version were examined on a sample of normal and clinically referred adolescents. The CDS and CDS-A discriminated adequately between clinical and non-clinical Ss, as well as between depressed and non-depressed. Only the CDS discriminated between depressed and 'sad', i.e. parental report did not discriminate between these two groups. A high correlation was found between the CDS and the Children's Depression Inventory. Internal consistency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 9 publications
3
35
2
1
Order By: Relevance
“…The findings of the present investigation are consistent with a number of earlier studies (Tonkin & Hudson, 1981;Bath & Middleton, 1985;Rotundo & Hensley, 1985) in indicating the need for revision of the current CDS norms. As noted earlier, application of the current guidelines for interpretation of CDS scores classified many nondepressed children as depressed.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The findings of the present investigation are consistent with a number of earlier studies (Tonkin & Hudson, 1981;Bath & Middleton, 1985;Rotundo & Hensley, 1985) in indicating the need for revision of the current CDS norms. As noted earlier, application of the current guidelines for interpretation of CDS scores classified many nondepressed children as depressed.…”
Section: Discussionsupporting
confidence: 94%
“…But there are indications that the age of the child may influence agreement patterns. Parents of adolescents have been found to underestimate consistently their child's depression (Moretti et al, 1985;Rotundo & Hensley, 1985). The present findings suggest that a similar phenomenon does not operate with prepubertal children and their parents.…”
Section: Discussioncontrasting
confidence: 52%
“…Test-retest reliability has been tested and was found to be 0.74 (Tisher, Lang-Takac, & Lang, 1992). Additionally, the CDS has been found to be moderately correlated to other measures of depression, such as the CDS and CDI (r = 0.48-0.84; Kazdin, 1987;Knight, Hensley, & Waters, 1988;Rotundo & Hensley, 1985). The correlation between parent and child ratings is very poor (r = 0.04; Kazdin, 1987).…”
Section: Children's Depression Scale (Cds)mentioning
confidence: 99%
“…Ivens & Rehm, 1988;Kazdin etal, 1983b;Reynolds, Anderson & Bartell, 1985;Rotundo & Hensley, 1985). Several studies have shown that alternative measures of childhood depression correlate with each other (e.g.…”
Section: Preschoolhigh Schoolmentioning
confidence: 99%